2021
DOI: 10.3390/plants10071334
|View full text |Cite
|
Sign up to set email alerts
|

Cassia fistula Leaves; UHPLC-QTOF-MS/MS Based Metabolite Profiling and Molecular Docking Insights to Explore Bioactives Role towards Inhibition of Pancreatic Lipase

Abstract: The present work was aimed at investigating hydroethanolic leaf extracts of Cassia fistula for their antioxidant and pancreatic lipase (PL) enzyme inhibitory properties. The most active extract was selected to profile the phytoconstituents by UHPLC-QTOF-MS/MS technique. Among the tested extracts, the 80% hydroethanolic extract exhibited the maximum levels of total phenolic and flavonoid contents (TPC and TFC) with a contribution of 201.3 ± 2.6 mg of gallic acid equivalent per gram of extract (GAE/g extract), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Molecular docking is a required method in structure-based drug design that estimates the binding affinity between two molecules. This binding nature assists in describing the critical biochemical processes related [39]. The present research investigation has identified the potential of Moscatilin as a promising drug candidate after the comparison of all the ADMET of this bibenzyl compound with the clinical drugs of the study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Molecular docking is a required method in structure-based drug design that estimates the binding affinity between two molecules. This binding nature assists in describing the critical biochemical processes related [39]. The present research investigation has identified the potential of Moscatilin as a promising drug candidate after the comparison of all the ADMET of this bibenzyl compound with the clinical drugs of the study.…”
Section: Discussionmentioning
confidence: 85%
“…Molecular docking is a required method in structure-based drug design that estimates the binding affinity between two molecules. This binding nature assists in describing the critical biochemical processes related [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this technique can be employed for the qualitative/quantitative analysis of known/unknown compounds from natural sources, especially from medicinal plants. No other technique combination can currently offer this versatility, separation efficiency, and user-friendliness while studying the separation and identification of bioactive compounds from the natural sources [13] . Thus, in the current study, we employed the LC-QTOF-MS method to quantify and identify the bioactive phytochemicals present in the various seed extracts of C. bonduc.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous extract showed prominent pancreatic lipase inhibitory potential in a dose-dependent manner, ranging from 12 to 46%, with maximum inhibitory activity at a concentration of 25 µg/ml. In another study, hydroethanolic leaf extract of C. stula exhibited pancreatic lipase inhibitory activity with an IC 50 of 30.5 ± 2.8 µg/ml and 17.31 ± 1.18 µg/ml [53]. Also, the n-hexane leaf extract of C. bakeriana Craib showed high inhibition of pancreatic lipase activity with an IC 50 of 25.27 ± 8.78 µg/ml [54].…”
Section: Anti-obesity Activity Of Cfl-aunpsmentioning
confidence: 99%